PENERAPAN KOMUNIKASI INTERPERSONAL KEPALA MADRASAH DALAM MENINGATKAN KINERJA GURU - Mazdayani, Mazdayani; Marlini, Marlini; Sugiratu, Andi (JMPA (Jurnal Manajemen Pendidikan Al-Multazam), 2023)
Interpersonal communication is communication between two or more people face to face, and has the possibility of each participant catching a reaction to the message conveyed. The type of research used was descriptive qualitative. The steps to determine the data source were: informants who were directly involved in this research problem, including the head of the madrasah and the teachers of Madrasah Tsanawiyah Baitul Ulum Suoh West Lampung. The results of the research show that the implementation of interpersonal communication by the head of the madrasah in improving the performance of teaching and education staff at MTs Baitul Ulum Tuguratu, the implementation of interpersonal communication by the head of the madrasah has gone well, this can be seen through the communication process of the head of the madrasah which can be said to be carried out quite smoothly at the madrasah.